Cybercrime: An Empirical Study of its Impact on Society- A Case Study of Chemistry Students - Al-Ani, Ahmed; Yousif, Ahmed A; Ahmed, Waled Abdo; Yousif, Emad A (Chemistry Education Department, 2024)
Cybercrime is considered one of the most significant crimes effecting people and society. Computer network are involved in this type of crime, with various hackers participating. Through such crime, identities and much information of the victims are stolen. Many students, especially international students and young individuals, fall victim to this fraud. This study focuses on raising awareness among people to avoid scammer’s link or unknown websites that seek to obtain their information. This will be achieved by organizing different questionnaires by teaching staff at one of the Iraqi Universities in this field, to be answered by undergraduate and postgraduate students. The statistical analysis conducted on this group showed that students are more educated and aware, making them less likely to fall victim to these types of crime. This is a result of the knowledge and skills these students acquired through technology and various sessions and training at universities or other resources.